Chromosomal level reference genome of Tachypleus tridentatus provides insights into evolution and adaptation of horseshoe crabs. (20th April 2019) - Gong, Li; Fan, Guangyi; Ren, Yandong; Chen, Yongjiu; Qiu, Qiang; Liu, Liqin; Qin, Yanli; Liu, Bingjian; Jiang, Lihua; Li, Haorong; Zeng, Yan; Gao, Qionghua; et al.
Abstract: Horseshoe crabs including Tachypleus tridentatus are a group of marine arthropods and living fossil species which have existed on the earth for 500 million years. However, the genetic mechanisms underlying their unique adaptive ability are still unclear. Here, we assembled the first chromosome‐level T. tridentatus genome, and proved that this genome is of high quality with contig N50 1.69 Mb. By comparison with other arthropods, some gene families of T. tridentatus experienced significant expansion, which are related to several signaling pathways, endonuclease activities, and metabolic processes. Based on the results of comparative analysis of genomics and 27 transcriptomes from nine tissues, we found that the expanded Dscam genes are located at key hub positions of immune network. Furthermore, the Dscam genes showed higher levels of expression in the yellow connective tissue (the birthplace of blood cells with strong differentiation capability) than the other eight tissues. Besides, the Dscam genes are positively correlated with the expression of the core immunity gene, clotting factor B, which is involved in the coagulation cascade reaction. The effective and unusual immune ability endowed by the expansion and expression of Dscam genes in the horseshoe crab may be a factor that makes the species have a strong environmental adaptability within 500 million years. The high quality chromosome level genome of a horseshoe crab and unique genomic features reported in this study provide important data resources for future studies on the evolution of marine ecological systems.